The shaping and picturing of the `Cape' and the `other(s)' : representation of the colony, its indigenous inhabitants and Islam during the Dutch and British colonial periods at the Cape (17th-19th centuries). - Toffah, Tariq. (My University, 2014)
Th e Dutch (VOC) trading empire of the seventeenth and eighteenth centuries brought with it to South Africa not only the world of powerful merchant capitalism, but it would also construct a new imaginative geography and order of the land to that which had been known by its ancient inhabitants, wherein the very idea of the land would be rewritten. Many aspects of this new geography would be refl ected in representation during VOC rule in the Cape colony, in its maps, pictures and drawings. Within this picturing of the land, the rival indigenous presence as well as the colony’s non-settlers inhabitants—both of whom formed colonial ‘others’—would also be depicted; although typically this visibility would be carefully measured and managed in complex ways in both offi cial and popular artistic representation. While offi cial colonial and apartheid archives in South Africa lack suffi cient, meaningful representation of marginalised groups such as blacks, slaves, Muslims, and indigenous people, the visual sources wherein such groups are depicted constitute another source of archive which has still only begun to be explored comparatively and as a body of images. Th rough visual sources, the study analyses fi rstly the discursive, imaginative, and physical appropriation of landscape as represented in Dutch and British colonial-period maps and pictures in the seventeenth to nineteenth centuries. Secondly it explores the representation of colonial ‘others’ who are depicted therein, and to what extent it may be possible to recover some aspects of marginalised narratives and spatial practices. Islam at the Cape, whose history dates back to the very beginning of European settlement but which was offi cially proscribed for the most of the colonial period, also forms an important component of the study, as a case study of such ‘liminal’ narratives and landscapes.
Keywords: Architecture--South Africa--History--19 century.